The bivalve-bearing carbonate platform on the east Tethys during the middle Eocene and its response to the Tethys transgression - Fang, Shaobo; Xi, Dangpeng; Sun, Qi; Li, Dalei; Yang, Zhangzhang; Liu, Dan; Wu, Yuyang; Jiang, Tian; Wan, Xiaoqiao (Frontiers in Earth Science, 2024)
The Eocene was a typical greenhouse climate period in the history of the Earth, with a high global sea level and extensive carbonate deposits developed in Tethys. During the Eocene, a carbonate platform was deposited in the western Tarim Basin, which belongs to the easternmost Tethys. However, the details of this carbonate platform and its complications for paleoecology and paleoclimate are still unclear. This research focuses on the bivalve-bearing carbonates of the Kalataer Formation in the western Tarim Basin, and detailed analyses of microfacies, biostratigraphy, paleoecology, and sea-level change were carried out. The bivalves of the Kalataer Formation are dominated by the Ostrea (Turkostrea) strictiplicata, Ostrea (Turkostrea) cizancourti, Ostrea (Turkostrea) strictiplicata, Ostrea (Turkostrea) strictiplicata, and Sokolowia buhsii, and the age is middle Lutetian of the Eocene. The biota of the Kalataer Formation mainly lives in open shallow sea environments, with medium to low energy and rich nutrients and oxygen, representing a typical shallow marine ecosystem of the carbonate platform. Microfacies and paleoecology indicate a large marine transgression event occurred in the western Tarim Basin during the middle Eocene.